(untitled) (KONFERENSIYA, 2026)
In the era of globalization and digital communication, the ability of students to communicate effectively in English is no longer limited to linguistic competence alone. It requires the formation of a communication culture that integrates psychological readiness, socio-emotional intelligence, and pedagogical support. This article explores the core psychological and pedagogical mechanisms that contribute to the development of English-based communication culture among students. It highlights the role of motivation, self-confidence, emotional climate, interactive teaching strategies, and digital tools in constructing communicative competence that aligns with modern educational demands.